1995
DOI: 10.1021/bp00034a002
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Bioremediation of Xenobiotic Compounds by the White‐Rot Fungus Phanerochaete chrysosporium

Abstract: The white‐rot fungi produce an unusual enzyme system, characterized by a specialized group of peroxidases, that catalyzes the degradation of the complex plant polymer lignin. This ligninolytic system shows a high degree of nonspecificity and oxidizes a very large variety of compounds in addition to lignin. Among these compounds are numerous environmental pollutants. Thus, the white‐rot fungi show considerable promise as bioremediation agents for use in the restoration of environments contaminated by xenobiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(68 citation statements)
references
References 109 publications
0
67
0
1
Order By: Relevance
“…P. chrysosporium was used as a reference fungus because it has been extensively applied as a model organism to study the physiological requirements and enzymes required for lignin and toxic biodegradation (Paszczynski and Crawford 1995). …”
Section: Resultsmentioning
confidence: 99%
“…P. chrysosporium was used as a reference fungus because it has been extensively applied as a model organism to study the physiological requirements and enzymes required for lignin and toxic biodegradation (Paszczynski and Crawford 1995). …”
Section: Resultsmentioning
confidence: 99%
“…Researchers are now focusing on white rot fungi for use in bioremediation processes since these organisms have the ability to degrade a wide range of environmental pollutions (Fu and Viraraghavan, 2001;Paszczynski and Crawford, 1995;Pointing, 2001;Shah and Nerud, 2002). The decolorization can be achieved either by adsorption or oxidative degradation by the enzymes (Fu and Viraraghavan, 2001;Knapp et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…glycines in the process of decolorization of anthraquinone dyes: RBBR and Poly R-478. Lignin peroxidase next to laccase was accepted to be the most important ligninolytic enzyme of white-rot basidiomycetes (Paszczyński and Crawford 1995;Robinson et al 2001;Martinez et al 2005). In the course of our study, we found that the level of LiP activity reached highest value in cultures of microfungi with lignin.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…Participation of the non-specific HRP-like peroxidase in the biodegradation of post-industrial of lignin was reported in the paper by Korniłłowicz-Kowalska et al (2008) concerning the anamorphic stadium of B. adusta CCBAS 930. In cultures of numerous lignin-degrading white-rot fungi, the manganese-dependent peroxidase is also detected (Paszczyński and Crawford 1995;Martinez et al 2005). The lignin-(LiP) and manganese-dependent (MnP) peroxidases were produced also by 23 strains of ascomycetes degrading lignin-cellulose, in particular from the genus Coniochaeta (Lopez et al 2007).…”
Section: Enzyme Activitiesmentioning
confidence: 99%